The PAU survey: measurements of the 4000 Å spectral break with narrow-band photometry. Issue 1 (23rd May 2022) - Renard, Pablo; Siudek, Malgorzata; Eriksen, Martin B; Cabayol, Laura; Cai, Zheng; Carretero, Jorge; Casas, Ricard; Castander, Francisco J; Fernandez, Enrique; García-Bellido, Juan; Gaztanaga, Enrique; Hoekstra, Henk; et al.
ABSTRACT: The D4000 spectral break index is one of the most important features in the visible spectrum, as it is a proxy for stellar ages and is also used in galaxy classification. However, its direct measurement has always been reserved to spectroscopy. Here, we present a general method to directly measure the D4000 with narrow-band (NB) photometry; it has been validated using realistic simulations, and then evaluated with PAUS NBs, cross-matched with VIPERS spectra ( i AB < 22.5, 0.562 < z < 0.967). We also reconstruct the D4000 with the SED-fitting code cigale ; the use of PAUS NBs instead of broad-bands significantly improves the SED fitting results. For D4000n, the direct measurement has SNR 4, but we find that for i AB < 21 all direct D4000 measurements have SNR3 . The cigale D4000n has SNR 20, but underestimates the error by >50 per cent. Furthermore, the direct method recreates well the D4000–SFR relation, as well as the D4000–mass relation for blue galaxies (for red galaxies, selection effects impact the results). On the other hand, cigale accurately classifies galaxies into red and blue populations. We conclude that the direct measurement of D4000 with narrow-band photometry is a promising tool to determine average properties of galaxy samples, with results compatible with spectroscopy.